Penyediaan Barang Milik Negara Berbasis Biaya Kepemilikan Total - Rokhmat Taufiq Hidayat; Resi Ariyasa Qadri (Institut Ilmu Sosial dan Manajemen STIAMI, 2020)
The procurement of government fixed assets in the form of buildings, business vehicles, and others has not taken into account the entire costs associated with the purchase of fixed assets. The total cost of ownership scheme offers a concept that takes into account the entire costs associated with the purchase, use, maintenance, and disposal of assets.This study aims to develop a conceptual model based on the assumption that the total cost of ownership can be used by the government in implementing fixed asset capital spending. Through this research it is hoped that the government can improve the efficiency of procurement of fixed assets through the implementation of the total cost ownership scheme.The method used in this study is the method of literature study by collecting some of the previous research results related to the theory and practice of total cost ownership. The resulting insights from the previous study were then analyzed using theme analysis for abstraction, thus generating a conceptual model of total ownership cost for the procurement of government fixed assets. The result of this study is a general model proposal for the assessment of total cost of ownership which includes a calculation of the total cost associated with the goods to be purchased by the government at each stage of decision-making, from the search and selection stages to the end of the term